Is There a Common Aetiology for Dyslexia, Visual Stress, and Pattern Glare? - Longhurst, Robert J. (Optometry & Visual Performance, 2017)
This paper discusses the current understanding of dyslexia - the many contrasting definitions of the condition and the numerous theories regarding its aetiology. Visual stress and pattern glare are also discussed, and an attempt is made to find a common link between dyslexia and these two syndromes. An argument is then made for the term dyslexia being a misnomer and dyslexia, visual stress, and pattern glare all being related in terms of a magnocellular deficit and/or a dorsal stream processing disorder. Coloured overlays and tinted lenses are also briefly discussed in the context of these disorders.